(untitled) (Literary Voice, 2024)
The paper analyses the relationship between queer and comics, with a particular emphasis on Maia Kobabe’s graphic memoir Gender Queer: A Memoir. It explores the narrative significance of comics and the convergence of queerness within the medium, framed within the theoretical frameworks of Scott McCloud, Richard Walsh, Ramzi Fawaz, and Darieck Scott. The primary objective of the study is to demonstrate how words and images interact to communicate Maia’s gender and sexual identities in a way that defies accepted cultural norms. It analyses and exhibits the ability of the visual narrative to convey nuanced facets of queer identity, ranging from representations of physical discomfort during medical exams to the presentation of romantic fantasies defying binary gender norms. The paper concludes that Maia employs an effective tool to convey the subtleties of eir queer identity through the symbiotic relationship between words and pictures, based on a careful analysis of eir narrative. Beyond the confines of conventional language, a more comprehensive expression of gender and sexuality is made possible by the interaction of words and images.